Mencari Model Pengembangan Kapasitas Lembaga Diklat Daerah Yang Efektif - Rahmat Suparman (Jurnal Wacana Kinerja: Kajian Praktis-Akademis Kinerja dan Administrasi Pelayanan Publik, 2008)
Training organisation (TO) has a very strategic role in developing the quality of human resource of Indonesian government apparatus. The many changing policies concerning the existence of TO has always been the main issues in building and managing TO, especially in local government context. This phenomenon has raised the issue of how and when to start developing the capacity of TO located in provincial or local governments. To start with NIPA Bandung regional office has conducted a research on identifying effective models of TO capacity building. This article is the result of the research and highlighted that there are three development models for TO, namely, expansion, equilibrium and survival models for high, medium and low capacity TO respectively. This research concluded that NIPA – as the supervising body for public service training – should revise its policy on evaluating the capacity of TO, especially the policy on accrediting and certifying TO.